Study on Flow Field and Fluid Structure Coupling Characteristics of Slide Valve Based on New Combined Groove Structure - ZHANGYang; LIJianying; WANGXiaojing; ZHANGQizheng; PENGChen (Journal of Harbin University of Science and Technology)
Thestructureof spool throttlegrooveof hydraulicspool valvehasadirect influenceon thestressdeformationof spool andthedistributionof internal flowfield. Inthispaper,taking4WE6Etypechange-overvalveastheresearchobject,anewcombined groovestructureisproposedonthetraditional spool throttlegroovestructureinorder toimprovethedynamicandstaticperformanceof thechange-overvalve. Fluent software andWorkbenchplatformareused to simulate internal flowfieldand fluid-solidcoupling for different spool structures. Then the flow field and stress deformation of spool with different structure are analyzed and studied quantitatively. Theflowrateandpressureof flowfield invalveandpressuredistributiononspool surfacearestudied indetail. The resultsshowthat thespoolvalvewiththenewcombinedgroovestructurecansignificantlyimprovetheflowfielddistributioninsidethe spoolandeffectivelyreducethespooldeformation,thus improvingthedynamicandstaticperformanceof thechange-overvalve.